Diluted magnetic layered semiconductor InSe:Mn with high Curie temperature - Lashkarev, G.V.; Sichkovskyi, V.I.; Radchenko, M.V.; Aleshkevych, P.; Dmitriev, O.I.; Butorin, P.E.; Kovalyuk, Z.D.; Szymczak, R.; Slawska-Waniewska, A.; Nedelko, N.; Yakiela, R.; Balagurov, A.M.; et al. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
We present a detailed study of layered semiconductor InSe doped with Mn. Xray
and neutron diffraction analyses of (In,Mn)Se single crystals show the presence of a
main phase as In₁−xMnxSe solid solution, the second antiferromagnetic MnSe phase,
and traces of In₄ Se₃ Magnetic measurements reveal ferromagnetic behavior of (In,Mn)Se with the Curie temperature about 800 K. The ferromagnetic cluster model and exchange interaction via 2D electron gas, as the reasons of spontaneous magnetization, are discussed. The dramatic transformation of (In,Mn)Se electron spin resonance (ESR) spectra as a function of temperature is revealed. At the magnetic field perpendicular to crystallographic c axis, a low-field line within the temperature range 70 down to 4.7 K is observed. It shifts to smaller magnetic fields with temperature decrease. Neutron diffraction studies reveal the strong rise for one of the reflection peaks with temperature decrease in the same temperature region where ESR spectra transformation occurs. This peak corresponds to double MnSe interplanar distance in the [111] direction what is a period of its magnetic lattice. Magnetic structure of (In,Mn)Se single crystal is discussed.